On the correlation of surface charge and energy in non‐thermal plasma‐treated polyethylene. (4th August 2014) - López‐García, Jorge; Lehocký, Marian; Humpolíček, Petr; Novák, Igor
<x xml:space="preserve">Abstract</x> Non‐thermal non‐equilibrium oxidative air 40‐kHz frequency, 13.56‐MHz radiofrequency and 2.46‐GHz microwave discharge plasma treatment were used for modifying low‐density polyethylene foils. The untreated and treated samples were chemically characterised by X‐ray photoelectron spectroscopy. In order to estimate the extent of the plasma sources at distinct treatment times, surface charge and energy were determined by zeta potential (ζ) and surface tension measurements. In addition, the isoelectric points (IEPs) of the studied samples were ascertained, and surface property variations were appraised by ageing time. The overall outcome indicated that ζ‐potential and surface energy progressively changed after each treatment, as well as the influences of ageing on surface features, the IEP shifting to lower pH values and how all of these changes are associated with the new surface chemistry. This contribution seeks to shed light on topics related to polymer science and plasma‐based strategies for surface modification. Copyright © 2014 John Wiley & Sons, Ltd.